Semi‐perfluoroalkylated perylene diimides for conjugated polymers with high molecular weight and high electron mobility. Issue 1 (15th October 2017) - Cai, Chunsheng; Wan, Ji; Zhang, Youdi; Yuan, Zhongyi; Huang, Qingfang; Xu, Guodong; Hu, Yu; Zhao, Xiaohong; Chen, Yiwang
ABSTRACT: Perylene diimides (PDIs) and their derivatives are excellent semiconductors, while conjugated polymers based on PDIs have limited applications because of their low electron mobility ( μ e ) derived from low molecular weight. The reported maximum number‐average molecular weight ( M n ) of related polymers is only 21 kDa because PDIs have very poor solubility due to strong π–π stacking of their big planar conjugated cores. Herein, it is found that suitable semi‐perfluoroalkyl groups could enhance the solubility of PDIs significantly, and a series of semi‐perfluoroalkyl modified conjugated polymers with high molecular weight and electron mobility were synthesized. The maximum M n reaches 94.8 kDa [P(4CF 8CH ‐PDI‐T2)HW ]. In their space‐charge‐limited current (SCLC) devices, all polymers exhibit typical characters of electron transporting semiconductors, and the highest μ e is up to 8.40 × 10 −3 cm 2 V −1 s −1 [P(4CF 8CH ‐PDI‐T2)HW ], which is similar as that of widely used electron transporting semiconductor PC61 BM (6.41 × 10 −3 cm 2 V −1 s −1 ). © 2017 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2018, 56, 116–124 Abstract : Suitable semi‐perfluoroalkyl chains can improve the solubility of perylene diimide (PDI) significantly. In this work, a series of semi‐perfluoroalkyl‐modified conjugated polymers based on PDI with high molecular weight and electron mobility have been synthesized. The impacts of semi‐perfluoroalkyl groups on the properties of the conjugated polymers have been investigated. Owing to low LUMO energy levels, strong absorptions, and high electron mobility, these polymers are excellent polymeric acceptors.